Research and Development: Model of Clinical Collaborative Supervision for Scientific Based English Instruction - Supriyono Supriyono; Hesty Puspita Sari (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This research aimed to establish an instructional supervision model for scientific-based English instruction at Islamic Junior Boarding Schools. Research questions were stated as to how was the formulation of the model. This research employed Research and Development with three phases of (1) foundational study seeking the potencies and problems using policy analysis, field study, and theoretical review; (2) design and development study by designing the hypothetical model and developing the model formulation to be validated; and (3) Try out the study by doing one group pre-post experimental and perceptional studies. Finally, the model was established informs of model book and tutorial usage. The model combined principles of clinical Supervision and collaborative orientation to control, which were compatible with the behavioural characteristic of Islamic Boarding Junior High Schools in a pesantren environment. This model obtained score validation of 89 %, categorized as valid, can be used without revision. While the pre-assessment score was 2.60 and the post-assessment score was 3.39with, the t-test was -7.0886on significant 0.05 and t table 2.447. This model was concluded to be practical and applicable to use as a Scientific Based English Instruction Supervision for Islamic Boarding Junior High Schools.